Membangun keluarga sakinah: Analisis upaya KUA Kecamatan Bungah, Kabupaten Gresik - Akbarsyah Izzul Haq, Raffly; Velayati, Naily (Prodi Hukum Keluarga Islam Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2024)
This research discusses the definition of a sakinah family and the efforts made by the Religious Affairs Office (KUA) of Bungah District, Gresik Regency, in realizing a sakinah family, as well as the supporting and inhibiting factors that influence these efforts. The purpose of this study is to find out the efforts of the KUA of Bungah Sub-district in forming a sakinah family and to understand the factors that support and hinder its success. This research is a field study with a qualitative approach, which focuses on the efforts of the KUA of Bungah Sub-district in realizing a sakinah family as well as the supporting and inhibiting factors. The data used comes from primary and secondary data sources, with data collection methods through observation, interviews, and documentation. The results show that the efforts made by the KUA of Bungah Sub-district in realizing a sakinah family have a significant impact on family life in the region. These efforts provide great benefits to the community in building family harmony, as well as increasing knowledge and understanding of the sakinah family. This is evidenced by the high interest of the community in attending the socialization organized by the KUA of Bungah Sub-district, both in public recitation and in guidance activities for prospective brides. In addition, the decrease in divorce cases in the Bungah Sub-district area is an indicator of the success of the efforts made.